The impact of high-rise construction of urban buildings on the management of infrastructure, wastewater and urban waste with a construction management approach: Case example of Yasouj city - ali momeni manesh (مهندسی و مدیریت ساخت)
The aim of the current research is the impact of high-rise urban buildings on the management of infrastructure, wastewater and urban waste with a construction management approach (case example of Yasouj city). The intended research method in this thesis is based on the practical purpose and on the descriptive-analytical nature. The statistical population of this research is made up of all engineers who are members of the supervision of the engineering system of Yasouj city. Cochran's method was used for random sampling in order to select the number of samples. In this research, a designed questionnaire tool (standard questionnaire) was used, which is one of the most common data collection tools in the field method. whose validity and reliability have been confirmed under the supervision of relevant experts and professors. In this research, according to the assumptions of the research and the sample group, SPSS software was used in two levels of descriptive and inferential statistics to analyze the data of the current research. ArcGIS software is used to display data and draw maps. The results of the research indicate that: high-rise construction has an impact on the use of residential land, and due to the increase in the urban population, on the service use of this city, as well as on the use of roads and the urban traffic network of Yasouj city.